Modeling, Simulation and Testing of Atomization Temperature Change Point of Thermochromic Glass for Building Energy Saving - Kai, Zeng; YuDai, Liang; BaoRong, Zhang; Quan, Shi; JinBo, Wu; WeiJia, Wen (Frontiers in Materials, 2022)
Thermochromic glass possesses a great potential for reducing the energy demand and providing indoor comfort in the buildings. Suitable atomization temperature change point has a great influence on the application of thermochromic glass. Based on energy consumption simulations and theoretical calculations by introducing solar radiation in a transparent envelope, this paper investigates atomization temperature change point of thermochromic glass in hot summer and cold winter zone represented by Chongqing, showing that the suitable temperature change point of thermochromic glass is 39 ℃ with air conditioning and 42.9 ℃ without air conditioning. Furthermore, results of simulations and theoretical calculations are applied to a test model, revealing that thermochromic glass with the temperature change point of 42.9 ℃ compared with Low-E glass can reduce the temperature of sunlight room by up to 5 ℃ in the summer and displays a certain thermal insulation effect in winter.